2018
DOI: 10.1108/et-05-2017-0070
|View full text |Cite
|
Sign up to set email alerts
|

Work-integrated learning and the importance of peer support and sense of belonging

Abstract: Purpose The purpose of this paper is to explore the relationship between peer support and sense of belonging on the mental health and overall well-being, with a specific focus on comparing the perceptions of students in a work-integrated learning (WIL) program to those in a traditional non-WIL program. Design/methodology/approach Semi-structured group interviews were conducted with 25 participants, selected from a university with a WIL program. Interview data captured perceptions of peer support, sense of be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…The importance of connectedness in schools as a means for promoting emotional well‐being is widely documented. With the help of supportive networks, children and young people are more likely to develop positive beliefs in themselves and feelings of competence and optimism (McBeath et al., 2018; McLoughlin et al., 2018). Schools play a key role in supporting bullied children and in promoting values that include vulnerable children in the peer group rather than excluding them.…”
Section: Is There a Way Forward?mentioning
confidence: 99%
“…The importance of connectedness in schools as a means for promoting emotional well‐being is widely documented. With the help of supportive networks, children and young people are more likely to develop positive beliefs in themselves and feelings of competence and optimism (McBeath et al., 2018; McLoughlin et al., 2018). Schools play a key role in supporting bullied children and in promoting values that include vulnerable children in the peer group rather than excluding them.…”
Section: Is There a Way Forward?mentioning
confidence: 99%
“…The COVID-19 pandemic has been creating sever pain to almost all areas of human life and economic activities. Realizing these facts, plenty of research rooms are open to examining its impacts, opportunities, and threats during pandemic period integrating multiple disciplines like peer support (McBeath et al, 2017), personal characteristics of students (Prevatt et al, 2011), self-control and time management (Kim & Seo, 2015;Mbuva, 2011), willingness to study (Leonard & Insch, 2005), student attention (Cao et al, 2020), acceptance of responsibility (Robinson, 1993), ability to concentrate (van den Bogaard, 2012), ability to react to change and mistake (Nonis et al, 2005), faculty attitudes (Yao et al, 2020), teaching strategies (Hattie, 2015) and many others . Similar study can be conducted longitudinally to judge further effectiveness and chaos regarding online mode during the pandemic period in developing countries.…”
Section: Way Forwardmentioning
confidence: 99%
“…Potential benefits of peer support include increased wellbeing and self-esteem, a sense of hope, companionship and improved social functioning (Davison et al 2012;Lawton-Smith 2013). Through semistructured interviews with students, McBeath, Maureen and Bohn (2017) reported that peer support could increase sense of belonging within the university community. Through sharing experiences, peer support may also provide greater social engagement and group identification (Naslund et al 2014).…”
mentioning
confidence: 99%
“…Through sharing experiences, peer support may also provide greater social engagement and group identification (Naslund et al 2014). Sense of group identification has been shown to predict lower levels of depression (Cruwys et al 2006), higher levels of life satisfaction (Sani et al 2012) and well-being (McBeath et al 2017).…”
mentioning
confidence: 99%